PENERAPAN SANKSI TERHADAP LARANGAN PERKAWINAN SEPUPU SEKALI MASYARAKAT DAYAK KANAYATN DI DUSUN PENAWAR DESA SEKILAP KECAMATAN MANDOR KABUPATEN LANDAK - NIM. A1011191041, KAROLINA KURARAH (Jurnal Fatwa Hukum, 2022)
AbstractMarriage custom is an important event for the life of the Dayak Kanayatn indigenous people. Marriage is a holy and sacred thing to establish a life and death relationship until death is separated so that there are customary prohibitions when carrying out marriages which are seen in the family tree. The prohibition of first cousin marriage is a marriage that is still related by blood, this is considered taboo because it does not respect the ancestors and hurts the hearts of indigenous peoples. The problem in this study is how the application of sanctions to couples who carry out first-cousin marriages has not been fully implemented in acc ordance with customary provisions, this is because there are several factors that trigger the occurrence of first-cousin marriages in that place.In this study the authors formulated the problem of "How to Apply Sanctions Against the Prohibition of Single Cousin Marriage in the Dayak Kanayatn Community in Penawar Hamlet, Sekilap Village, Mandor District, Landak Regency?". This study aims to get an overview regarding the implementation of the ban on first cousin marriages, to reveal the factors that cause first cousin marriages to occur, to explain and reveal the legal consequences for couples in imposing sanctions on first cousin marriages, to reveal the efforts of traditional Dayak Kanayatn functionaries related to the implementation of customary sanctions against the ban on first-cousin marriages. This study uses empirical research methods that are conceptualized as real behavior as social phenomena that are not written in social life relationships. The nature of this research is descriptive which gives a careful description of certain individuals or groups regarding the circumstances or symptoms that occur. Qualitative data analysis techniques systematize what is being researched and then arrange the results of the interviews to be able to present them back to others.Based on the results of the study, it can be concluded that the application of sanctions against first-cousin marriages in Penawar Hamlet, Sekilap Village, Foreman District, Landak Regency will be subject to sanctions against couples, but the application has not been fully implemented because they cannot fulfill the specified customary regulations. Factors causing the occurrence of first cousin marriages are factors of mutual love, education, economy, technology. The legal consequences for couples who perform cousin marriages are subject to traditional Pangarumpang'k sanctions, namely in the form of customary fines that have been determined by customary functionaries. Efforts made by customary functionaries for customary settlements through outreach to the community, especially the younger generation in Penawar Hamlet, Sekilap Village, Mandor District, Landak Regency.Keywords: Marriage Customary Prohibition/Customary Sanctions/ first-cousin AbstrakAdat Perkawinan merupakan peristiwa penting bagi kehidupan masyarakat adat Dayak Kanayatn. Perkawinan hal yang suci dan sakral untuk menjalin hubungan sehidup semati sampai maut memisahkan sehingga ada larangan-larangan adat ketika akan melaksanakan perkawinan yang dilihat dalam silsilah keluarga. Larangan perkawinan sepupu sekali merupakan perkawinan yang masih satu ikatan darah hal ini dianggap tabu karena tidak menghormati leluhur nenek moyang dan mencederai hati masyarakat adat. Adapun masalah dalam penelitian ini bagaimana penerapan sanksi kepada pasangan yang melakukan perkawinan sepupu sekali belum sepenuhnya dilaksanakan sesuai dengan ketentuan adat hal ini karena ada beberapa faktor yang menjadi pemicu terjadinya perkawinan sepupu sekali di tempat tersebut.Dalam penelitian ini penulis merumuskan masalah tentang "Bagaimana Penerapan Sanksi Terhadap Larangan Perkawinan Sepupu Sekali Masyarakat Dayak Kanayatn Di Dusun Penawar Desa Sekilap Kecamatan Mandor Kabupaten Landak?". Penelitian ini bertujuan untuk mendapatkan gambaran terkait pelaksanaan terhadap larangan perkawinan sepupu sekali, untuk mengungkapkan faktor penyebab terjadi perkawinan sepupu sekali, untuk menjelaskan dan mengungkapkan akibat hukum bagi pasangan dalam penerapan sanksi terhadap perkawinan sepupu sekali, untuk mengungkapkan upaya fungsionaris adat Dayak Kanayatn terkait dengan pelaksanaan penerapan sanksi adat terhadap larangan perkawinan sepupu sekali. Penelitian ini menggunakan metode penelitian empiris yang dikonsepkan sebagai perilaku nyata sebagai gejala sosial yang sifatnya tidak tertulis dalam hubungan hidup bermasyarakat. Sifat penelitian ini adalah deskriptif yang memberi gambaran secara cermat mengenai individu atau kelompok tertentu tentang keadaan atau gejala yang terjadi. Teknik analisis data secara kualitatif mensistematika apa yang sedang diteliti dan kemudian mengatur hasil wawancara untuk dapat menyajikan kembali pada orang lain.Berdasarkan hasil penelitian dapat disimpulkan bahwa pelaksanaan penerapan sanksi terhadap perkawinan sepupu sekali di Dusun Penawar Desa Sekilap Kecamatan Mandor Kabupaten Landak akan dikenakan sanksi kepada pasangan namun penerapannya masih belum terlaksana sepenuhnya dikarenakan tidak dapat memenuhi perada adat yang ditentukan. Faktor penyebab terjadinya perkawinan sepupu sekali adalah faktor saling cinta, pendidikan, Ekonomi, Teknologi. Akibat hukum bagi pasangan yang melakukan perkawinan sepupu sekali dikenakan sanksi adat Pangarumpang"™k yaitu berupa denda adat yang sudah ditentukan oleh fungsionaris adat. Upaya yang dilakukan Fungsionaris adat untuk melestarikan adat melalui sosialisasi kepada masyarakat khususnya generasi muda di Dusun Penawar Desa Sekilap Kecamatan Mandor Kabupaten Landak.Kata kunci : Larangan Adat Perkawinan/Sanksi Adat/Sepupu Sekali